Immunohistochemistry Analysis of P53 and Ki-67 Proteins in Oral Lichen Planus and Normal Oral Mucosa - F Agha-Hosseini; M Khalili; B Rohani (Iranian Journal of Public Health, 2009)
Background: Oral lichen planus (OLP) is a relatively common chronic inflammatory muco-cutaneous disease classified among the potentially malignant lesions of oral mucosa. In this study we evaluated tissue expression of p53، ki-67 in OLP compared to normal oral mucosa. Methods: Specimens (formalin-fixed and paraffin- embedded) of 44 lesions of OLP and 30 controls referred to immunohistochemistry (IHC) analysis for p53 and ki-67. Results of immunohistochemistry were statistically evaluated by means of Kolmogorov- Smirnov, Kruskal- Wallis and t-test. The level of statistical significance was established at P< 0.05. Results: This study included 44 patients with OLP (27 females and 17 males) and 30 subjects as control group (18 females and 12 males).The mean expression of p53 in patients with OLP was greater than subjects in control group. The mean expression of ki- 67 in patients with OLP was more than people in control group. These differences were statistically significant (P= 0.001). Conclusion: Since p53 and ki-67 extensively accepted as important biomarkers in diagnosis, prognosis and treatment of malignant and premalignant lesions, therefore high degree of presence of these biomarkers in chronic premalignant lesion like OLP can be a great helpful in its prognosis and suggested treatments.